Prevalence of periodontitis in Nuh (Haryana State): The most backward district of India - Amita Sharma; Parveen Ranga (Wolters Kluwer Medknow Publications, 2019)
Background: Majority of the Indian population suffers from oral health diseases, especially periodontitis. Clinical manifestations of the disease are most commonly seen after 35 years of age, which if left untreated will ultimately result in loss of the tooth. Materials and Methods: A total of 576 subjects of different age groups were selected from 11 villages of Nuh district by simple random selection. The demographic data and oral hygiene habits along with deleterious habits such as smoking, panmasala, and tobacco chewing were recorded. Community periodontal index of treatment need (CPITN) was recorded with the help of CPITN probe. Results: Deep pockets were observed in 45.6% of the participants and 26.2% of the sextants. Shallow pockets were observed in 38.3% of the participants and 36.4% of the sextants. Calculus had the highest score in15.6% of the participants and 49.15% of the sextants. An inference was drawn from the results that among 576 participants 72.89% of individuals needed TN2 whereas 26.23% of individuals needed TN3 and 0.65% of individuals needed TN1. Conclusions: Severity of periodontal disease increased with age. The severity of periodontitis was observed significantly more in smokers and tobacco chewers as compared to nonsmokers and nontobacco chewers, respectively.